Human bombing - a religious act - Ilyas, Mohammed (Journal of terrorism research, 2014)
The issue of human bombing, which is popularly known as suicide bombing has become important in the Western world since the 9/11 and 7/7 attacks. Since then the issue of human bombing has become important to academia, the media, and security experts. This interest has resulted in much literature attempting to explain why human bombings take place and what motivates the bombers; for instance, the works of Gambetta (2006); Pape (2006); Merari (2010); Hafez (2006, 2007); Wright (2007); Bloom (2005, 2010); Friedman (2005); and Khosrokhavar (2005).Publisher PD